2006
DOI: 10.1016/s1808-8694(15)31005-3
|View full text |Cite
|
Sign up to set email alerts
|

Pollen allergic disease: pollens and its major allergens

Abstract: Patients with grass pollen allergy, commonly called pollinosis, often present reactivity to pollen allergens from a number of grass species due to cross-reactivity of IgE antibodies to pollen proteins present in pollen grasses. In this context, Italian rye grass (Lolium multiflorum) pollen of the Poaceae family cultivated in Southern Brazil has been considered a major sensitizing agent in patients with pollinosis. In this region, Italian rye grass is capable of producing a great amount of pollen. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Currently, there is no commercial L. multiflorum extract, standardized or not, for clinical use in skin testing or immunotherapy. 27 In a Brazilian study, Goulart et al (using a prick test) observed 75% positivity for any type of allergens in patients with VKC. Dust and dust mite extracts (D. pteronyssinus and Dermatophagoides farinea) were the most frequent positives.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, there is no commercial L. multiflorum extract, standardized or not, for clinical use in skin testing or immunotherapy. 27 In a Brazilian study, Goulart et al (using a prick test) observed 75% positivity for any type of allergens in patients with VKC. Dust and dust mite extracts (D. pteronyssinus and Dermatophagoides farinea) were the most frequent positives.…”
Section: Discussionmentioning
confidence: 97%
“…Poaceae pollen include the wild and cultivated grass pollen, which were more abundant from June and December; pollen allergies at this period could be attributed partly to their higher antigenic load. Taketomi et al (2008) founded the pollen of Poaceae family as a major sensitizing agent in patients with pollinosis. D’Amato et al (2007) stated also that grass-induced pollinosis is the most common pollen allergy in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…These allergens may diffuse into the body from the upper respiratory tract or enter the body through intake of vast range of plant food or may cause external skin irritations [3–5]. Allergens present primarily in pollens, spores, and other plant associated products are responsible for symptoms like rhinoconjunctivitis, asthma, edema, urticarial, and anaphylaxis [6–8].…”
Section: Introductionmentioning
confidence: 99%